Prenatal maternal immune activation and brain development with relevance to psychiatric disorders - Scola, Gustavo; Duong, Angela (Neuroscience, 2017)
•Maternal infection is linked to increased risk of psychiatric disorders.•Maternal immune activation changes cytokine levels and brain morphology.•Altered cytokine levels are found in subjects with psychiatric disorders. Growing evidence from epidemiological studies strongly suggests maternal infection as a risk factor for psychiatric disorders including bipolar disorder, schizophrenia, and autism. Animal studies support this association and demonstrate that maternal immune activation (MIA) changes brain morphology and inflammatory cytokines in the adult offspring. Evidence for changes in inflammatory cytokines is also demonstrated in human post-mortem brain and peripheral blood studies from subjects with psychiatric disorders. This perspective briefly highlights convincing evidence from epidemiological, preclinical and human pathological studies to support the role of MIA in major psychiatric disorders. A better understanding of the link between MIA and brain development in psychiatric disorders will lead to the development of novel immunomodulatory interventions for individuals at risk for psychiatric disorders.